A heat storage polyamide composition and its preparation method and application

By PP grafting maleic anhydride coating on the phase change microcapsules and using a compatible agent in combination with the polyamide resin, the problem of insufficient compatibility and heat resistance between the phase change microcapsules and the polyamide resin is solved, and the high heat storage performance and good processing performance of the heat storage polyamide composition are achieved.

CN117430944BActive Publication Date: 2025-03-25JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311622576.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-03-25
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

In the prior art, the overall compatibility and heat resistance of phase change microcapsules with polyamide resins are insufficient, resulting in poor heat storage performance of the heat storage polyamide composition, which is difficult to meet the needs of electronic and electrical shells and other fields.

Method used

By using PP grafted maleic anhydride to coat the phase-change microcapsules with polyurethane, the compatibility and processing performance are significantly improved, and they are introduced into a polyamide resin substrate, and the heat storage polyamide composition is prepared in combination with a compatibility agent.

Benefits of technology

The high heat storage performance of the heat storage polyamide composition is achieved, the latent heat of phase change is not less than 6.9 J/g, the temperature difference change is not higher than 57°C, and the extractable content is significantly reduced, not more than 4.9%, which significantly improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004579701350000011
    Figure BDA0004579701350000011
  • Figure BDA0004579701350000021
    Figure BDA0004579701350000021
  • Figure BDA0004579701350000022
    Figure BDA0004579701350000022
Patent Text Reader

Abstract

The present invention discloses a heat storage polyamide composition and its preparation method and application. The heat storage polyamide composition comprises the following components calculated in parts by weight: 23 to 75 parts of polyamide resin; 5 to 25 parts of coated phase change microcapsules; 20 to 50 parts of compatibilizers; 0 to 10 parts of processing aids; the coated phase change microcapsules are obtained by coating the phase change microcapsules with PP grafted maleic anhydride; the shell of the phase change microcapsules is polyurethane. The present invention can significantly improve the compatibility and processing performance of the phase change microcapsules after coating the phase change microcapsules with PP grafted maleic anhydride, and introduce it into the polyamide resin system substrate. The synergistic effect with the compatibilizer can obtain a heat storage polyamide composition with high phase change latent heat, low temperature difference and good processing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of engineering plastics, and more specifically to a heat storage polyamide composition, a preparation method and application thereof. Background Art

[0002] Phase change energy storage materials are materials that use the heat absorption and release effects of matter during phase change to store thermal energy and regulate temperature. Among them, microencapsulated phase change materials have a large heat transfer area, a relatively stable structure, etc., and have advantages in thermal conductivity, leakage prevention, and volume expansion.

[0003] Polyamide resin has good mechanical strength, good heat resistance, self-lubricating property, and is resistant to oil, weak acid, alkali and general solvents. Due to its excellent solvent resistance, mechanical properties, processing performance and heat resistance, polyamide resin is widely used in rail transportation, sports equipment, household appliances and other fields. Especially when used in electronic and electrical housings, it is generally required to have good heat storage function to achieve good heat transfer and heat conduction effect. The heat storage function of the material can usually be achieved by adding phase change microcapsules. However, due to the compatibility and heat resistance of phase change microcapsules with the overall material, the research on heat storage polyamide compositions has become a difficult point. Therefore, the art needs to develop a polyamide composition with heat storage capacity. Summary of the invention

[0004] The purpose of the present invention is to provide a heat storage polyamide composition in order to overcome the defects or shortcomings in the above-mentioned prior art, and the composition has good heat storage performance.

[0005] Another object of the present invention is to provide a method for preparing the heat storage polyamide composition.

[0006] Another object of the present invention is to provide application of the heat storage polyamide composition in the fields of building materials and energy storage materials.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A heat storage polyamide composition comprises the following components calculated in parts by weight:

[0009]

[0010] The coated phase-change microcapsules are PP grafted maleic anhydride coated phase-change microcapsules; and the shell of the phase-change microcapsules is polyurethane.

[0011] After a large number of experimental studies, the inventors found that by using PP grafted maleic anhydride to coat the polyurethane phase change microcapsules, the PP grafted maleic anhydride can combine with the carbamate groups on the surface of the phase change microcapsules, which can significantly improve their compatibility and processing performance; introducing it into the polyamide resin substrate and synergizing with the compatibilizer can obtain a heat storage polyamide composition with high phase change latent heat, low temperature difference and good processing performance.

[0012] Furthermore, the heat storage polyamide composition comprises the following components calculated in parts by weight:

[0013]

[0014] Furthermore, the coating rate of the coated phase change microcapsules is 3-6%.

[0015] Furthermore, the shell of the phase-change microcapsule is metal ion cross-linked polyurethane.

[0016] In a specific embodiment, the metal ion is a zinc ion or a zirconium ion.

[0017] Furthermore, the core material of the phase change microcapsule is alkane paraffin and / or higher fatty alcohol; the carbon number of the alkane is 18 to 30; the higher fatty alcohol is a monohydric alcohol with a carbon number greater than 12 and a mixture thereof.

[0018] The coated phase-change microcapsules involved in this application can be purchased from the market or can be homemade.

[0019] Furthermore, the preparation method of the coated phase change microcapsules is as follows:

[0020] Heat and mix water and phase change microcapsules, add PP grafted maleic anhydride and stir evenly, raise the temperature to 75-85°C and stir to react, then cool down, filter and dry in sequence to obtain coated phase change microcapsules.

[0021] The calculation method of coverage is as follows:

[0022] Covering rate = (mass of coated phase change microcapsules - mass of phase change microcapsules) / mass of phase change microcapsules × 100%.

[0023] Furthermore, the grafting rate of maleic anhydride in the PP grafted with maleic anhydride is 0.3-1.5%.

[0024] Furthermore, the method for determining the grafting rate of maleic anhydride is as follows:

[0025] Accurately weigh 1 g of the refined maleic anhydride grafted product and place it in a 500 mL conical flask. Pour in 100 mL of xylene and 10 mL of sodium hydroxide-methanol standard solution. Reflux at 135-140 ° C for 2 hours. Then pour the hot solution into a certain amount of acetone to precipitate and filter. Use phenolphthalein as an indicator and titrate with 0.1 mol / L HCl-ethanol solution to the endpoint. Perform a blank test and calculate the maleic anhydride content according to the formula.

[0026]

[0027] Where:

[0028] G: Grafting rate, %

[0029] V2: The volume of HCl-ethanol standard solution consumed in the blank experiment titration to the endpoint, mL

[0030] V1: The volume of HCl-ethanol standard solution consumed by the graft titration to the endpoint, mL

[0031] C: calibrated concentration of HCl-ethanol standard solution, mol / L

[0032] M: mass of grafted material, g

[0033] 98.06: Molecular weight of maleic anhydride, g / mol.

[0034] Furthermore, the mixing temperature is 45-55°C.

[0035] Furthermore, the mass ratio of the phase change microcapsules to the PP grafted maleic anhydride is 1:(0.05-0.2).

[0036] Furthermore, the stirring reaction time is 1 to 2 hours.

[0037] In the heat storage polyamide composition, the content of the coated phase change microcapsules is not less than 3wt%, for example but not limited to 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% and 20wt%, etc. Further, the content of the coated phase change microcapsules is 5 to 18wt%.

[0038] Furthermore, the content of the coated phase change microcapsules is 10-15wt%.

[0039] In the heat storage polyamide composition, the content of the polyamide resin is not less than 20wt%; the content of the polyamide resin accounts for more than 85wt% of the resin component content in the heat storage polyamide composition, for example but not limited to 90wt%, 95wt% and 100wt%.

[0040] The polyamide resin includes at least one of semi-aromatic polyamide and aliphatic polyamide. The semi-aromatic polyamide is selected from one or more of PA6T / 66, PA6I, PA6T / 6I, PA6T / M5T, PA9T, PA9T / 66, PA10T, PA10T / 66, PA10T / 10I, PA10T / 1010, PA12T and PA12I.

[0041] The aliphatic polyamide is selected from one or more of PA6, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA11, and PA12.

[0042] Furthermore, the compatibilizer is a maleic anhydride grafted product.

[0043] Furthermore, the compatibilizer is one or more of PP grafted maleic anhydride, POE grafted maleic anhydride or EPDM grafted maleic anhydride.

[0044] Furthermore, the compatibilizer is PP grafted maleic anhydride; the maleic anhydride grafting rate of the PP grafted maleic anhydride is 0.3-1.2%.

[0045] Furthermore, the processing aid includes a lubricant and / or an antioxidant.

[0046] In the present invention, the lubricant can be selected from commonly used lubricants according to the prior art, such as but not limited to one or more of ester lubricants, amide lubricants, stearic acid lubricants, hyperbranched polyesters or ethylene-acrylic acid copolymers.

[0047] Specifically, the ester lubricant is one or more of aliphatic stearate, oleic acid-based aliphatic polyester or meso-acid-based aliphatic polyester.

[0048] The amide lubricant is one or more of ethylene bis stearamide lubricant, oleamide lubricant, erucamide lubricant or stearamide lubricant.

[0049] The stearic acid lubricant is one or more of zinc stearate, magnesium stearate or tridecyl stearate.

[0050] In the present invention, the antioxidant may be selected from commonly used antioxidants according to the prior art, such as but not limited to one or more of hindered phenol antioxidants, hindered amine antioxidants or phosphorus-containing antioxidants.

[0051] Specifically, the hindered phenol antioxidant is one or more of β(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester or 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, tetrakis[β(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester or diethylene glycol bis[methyl 3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate].

[0052] The hindered amine antioxidant is one or more of tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate methyl ester, 1,3,5-(3,5-di-tert-butyl-4-hydroxyphenyl)-triazine-2,4,6(1H, 3H, 5H) trione or triethylene glycol ether-di(3-tert-butyl-4-hydroxy-methylphenyl) propionate.

[0053] The phosphorus-containing antioxidant is one or more of 2,4-di-tert-butylphenol (Irganox 168), bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol phosphite (PEP-36) or 627A.

[0054] The present invention provides a method for preparing the above-mentioned heat storage polyamide composition, comprising the following steps:

[0055] The polyamide resin, the coated phase change microcapsules, the compatibilizer and the processing aid are mixed, melt blended and extruded to granulate to obtain the heat storage polyamide composition.

[0056] Furthermore, the extrusion granulation is carried out in a twin-screw extruder.

[0057] Furthermore, the extrusion temperature is 200-240°C.

[0058] The present invention protects the application of the heat storage polyamide composition in the fields of building materials and energy storage materials.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] The invention provides a heat storage polyamide composition. Phase change microcapsules coated with PP grafted maleic anhydride are added into the polyamide composition. The compatibility and processing performance of the phase change microcapsules coated with PP grafted maleic anhydride are significantly improved. The heat storage polyamide composition prepared by combining with a compatibilizer has good heat storage effect, phase change latent heat is not less than 6.9 J / g, temperature difference change is not higher than 57°C, and extractable content is significantly reduced and does not exceed 4.9%, indicating that the phase change microcapsules have less internal material leakage and good processing performance. DETAILED DESCRIPTION

[0061] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0062] The raw materials used in the embodiments and comparative examples of the present invention are:

[0063] Polyamide resin:

[0064] Polyamide resin 1: PA6, HY2500A, Jiangsu Haiyang Chemical Fiber Co., Ltd.;

[0065] Polyamide resin 2: PA610, G120, Shandong Guangyin New Materials Co., Ltd.;

[0066] Phase change microcapsule 1: XB52, the shell is a metal ion cross-linked waterborne polyurethane (the metal ion is Zn 2+ ), the core material is alkane paraffin, Hefei Ruixue New Material Technology Co., Ltd.;

[0067] Phase change microcapsule 2: XB43, the shell is a metal ion cross-linked waterborne polyurethane (the metal ion is Zn 2+ ), the core material is polyethylene glycol, Hefei Ruixue New Material Technology Co., Ltd.;

[0068] Phase change microcapsule 3: XS50, shell is polystyrene, core material is alkane paraffin, Hefei Ruixue New Materials Technology Co., Ltd.;

[0069] PP grafted with maleic anhydride:

[0070] PP grafted maleic anhydride 1: PP-MAH-1, maleic anhydride grafting rate 0.3%, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;

[0071] PP grafted maleic anhydride 2: PP-MAH-2, maleic anhydride grafting rate 0.5%, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;

[0072] PP grafted maleic anhydride 3: PP-MAH-3, maleic anhydride grafting rate 0.8%, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;

[0073] PP grafted maleic anhydride 4, PP-MAH-4, maleic anhydride grafting rate is 1.2%, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;

[0074] POE grafted with maleic anhydride, POE-MAH-1, maleic anhydride grafting rate 0.6%, Shenyang Ketong Plastic Co., Ltd.;

[0075] Compatibilizer:

[0076] Compatibilizer 1: PP grafted maleic anhydride, PP-MAH-10, Foshan Nanhai Bochen Polymer New Materials Co., Ltd.;

[0077] Compatibilizer 2: POE grafted maleic anhydride, POE-MAH-10, Shenyang Ketong Plastic Co., Ltd.;

[0078] The coated phase change microcapsules described in the embodiments of the present invention are prepared by the following method according to the raw material dosages in Table 1:

[0079] Add 150mL of water and 50g of phase change microcapsules into a reactor equipped with a stirring and reflux device, heat to 50°C, add 2.5-10g of PP grafted maleic anhydride, stir rapidly for 10min, heat to 80°C, continue stirring and reacting for 1.5 hours, then cool to room temperature, filter and dry in sequence to obtain coated phase change microcapsules.

[0080] Table 1 Amount of raw materials used in coating phase change microcapsules 1 to 8

[0081]

[0082] Coated phase-change microcapsule 9: 50 g of phase-change microcapsule 1 and 5 g of POE-grafted maleic anhydride were used to prepare the microcapsule according to the above method, with a coating rate of 3.4%.

[0083] The calculation method of coverage is as follows:

[0084] Covering rate = (mass of coated phase change microcapsules - mass of phase change microcapsules) / mass of phase change microcapsules × 100%.

[0085] Coated phase change microcapsule 10: MQ silicone resin coated phase change microcapsule, the preparation method is the same as coated phase change microcapsule 1, the only difference is that MQ silicone resin is used instead of PP grafted maleic anhydride 1, and the coating rate is 3.5%.

[0086] Coated phase change microcapsule 11: 50 g of phase change microcapsule 3 and 5 g of PP grafted maleic anhydride 1 were used to prepare the microcapsule according to the above method, with a coating rate of 0.2%.

[0087] Processing aid: antioxidant, hindered phenol antioxidant Irganox 1098; lubricant: ethylene-acrylic acid copolymer, A-C540A, the lubricant and antioxidant are both commercially available, and Examples 1 to 14 and Comparative Examples 1 to 5 all use the same lubricant and antioxidant.

[0088] Examples 1 to 14 and Comparative Examples 1 to 5

[0089] According to the formulations in Tables 2 to 3, a heat storage polyamide composition was prepared according to the following preparation method:

[0090] The polyamide resin, coated phase change microcapsules, compatibilizer and processing aid are added into a twin-screw extruder, mixed, melt-blended and extruded to obtain a heat storage polyamide composition; the extrusion temperature is 200-240°C.

[0091] Table 2 Amount of each component in the heat storage polyamide composition in Examples 1 to 8 (parts by weight)

[0092]

[0093] Table 3 Amount of each component in the heat storage polyamide composition in Examples 9 to 14 (parts by weight)

[0094]

[0095]

[0096] Table 4 Amount of each component in the heat storage polyamide composition in Comparative Examples 1 to 5 (parts by weight)

[0097]

[0098] Performance Testing

[0099] 1. Test methods

[0100] The heat storage polyamide composition prepared above was subjected to performance tests:

[0101] (1) Latent heat of phase change: Using a differential scanning calorimeter, the heating rate was 10°C / min, and the melting enthalpy in the range of 35 to 65°C was calculated, which is the latent heat of phase change.

[0102] (2) Extractable content: Weigh equal amounts of the polyamide compositions in the examples and comparative examples and record them as initial mass;

[0103] Extract in 40°C acetone solution for 24h, then filter and dry to calculate the mass after drying, according to the extractable content = (initial mass - mass after drying) / initial mass × 100%;

[0104] (3) Temperature difference test: The heat storage polyamide composition prepared in each embodiment and comparative example was injection molded into a 100 mm*100 mm*3 mm square plate, which was vertically placed 20 cm below an infrared lamp and irradiated at a fixed power of 800 W for 5 min. Then, the surface temperature difference of the square plate was measured.

[0105] 2. Test results

[0106] The performance test results of the heat storage polyamide composition prepared by the above method are shown in Table 5.

[0107] Table 5 Performance test results of various embodiments and comparative examples

[0108] Latent heat of phase change (J / g) Extractable matter content (%) Temperature difference (℃) Example 1 12.9 1.9 40 Example 2 12.6 2.0 41 Example 3 13.4 2.1 39 Example 4 14.1 2.0 35 Example 5 13.1 2.0 40 Example 6 12.4 1.7 43 Example 7 13.3 1.8 40 Example 8 13.2 1.6 41 Example 9 12.8 1.9 41 Example 10 13.4 1.4 40 Embodiment 11 6.9 1.4 57 Example 12 7.1 1.1 54 Embodiment 13 25.1 2.3 36 Embodiment 14 9.6 4.9 53 Comparative Example 1 5.6 8.2 68 Comparative Example 2 4.2 7.7 73 Comparative Example 3 4.9 7.1 62 Comparative Example 4 3.3 9.6 78 Comparative Example 5 5.5 8.1 66

[0109] It can be seen from Table 5 that the heat storage performance and processing performance of the heat storage polyamide composition prepared in each embodiment of the present invention are significantly improved. Specifically, the latent heat of phase change is not less than 6.9 J / g, the temperature difference is not higher than 57°C, and the extractable content is significantly reduced, not exceeding 4.9%.

[0110] It can be seen from Examples 1 and 3 to 5 that when the PP grafted maleic anhydride grafting rate of the coated phase change microcapsules is adjusted to 0.5-1.0%, the obtained heat storage polyamide composition has a better effect. When the content of extractables is equivalent, it has a higher phase change latent heat and a lower temperature difference. The phase change latent heat is not less than 13.4 J / g, and the temperature difference is not higher than 39°C.

[0111] It can be seen from Example 1 and Example 14 that when PP grafted maleic anhydride is selected as a compatibilizer, the comprehensive performance of the obtained heat storage polyamide composition is better, and the heat storage effect and processing performance are significantly improved.

[0112] Based on Examples 1 to 14, when PP grafted maleic anhydride is selected as a compatibilizer and the added amount of coated microcapsules is 10%, the latent heat of phase change is not less than 12 J / g, the temperature difference is not higher than 45°C, and the extractable content is not higher than 3%.

[0113] It can be seen from Comparative Example 1 that when an equal amount of phase change microcapsules are used instead of coated phase change microcapsules, the comprehensive performance of the obtained heat storage polyamide composition is significantly reduced, the phase change latent heat is only 5.6 J / g, the temperature difference is as high as 68°C, and the extractable content is increased to 8.2%.

[0114] It can be seen from Comparative Example 2 that when the coated phase change microcapsules are obtained by coating the phase change microcapsules with POE grafted maleic anhydride, the comprehensive performance of the obtained heat storage polyamide composition is significantly reduced, the phase change latent heat is only 4.2 J / g, the temperature difference is as high as 73°C, and the extractable content is increased to 7.7%, which is significantly worse than that of the embodiment.

[0115] It can be seen from Comparative Example 3 that when phase change microcapsules are used and the amount of compatibilizer is increased, the comprehensive performance of the heat storage polyamide composition obtained is improved compared with Comparative Example 1 to a certain extent, but compared with the performance of the coated phase change microcapsules used in Example 1, it is still significantly worse, the phase change latent heat is only 4.9 J / g, the temperature difference is as high as 62°C, and the extractable content is increased to 7.1%, which is significantly worse than Example 1.

[0116] It can be seen from Comparative Example 4 that the comprehensive performance of the heat storage polyamide composition obtained by using ordinary commercially available MQ silicone resin to coat phase change microcapsules is significantly reduced, the phase change latent heat is only 3.3 J / g, the temperature difference is as high as 78°C, and the extractable content is increased to 9.6%, which is significantly worse than that of the embodiment.

[0117] It can be seen from Comparative Example 5 that when the shell of the phase change microcapsule is not polyurethane, the coating rate of the coated phase change microcapsule cannot be increased, which significantly reduces the comprehensive performance of the obtained heat storage polyamide composition, the phase change latent heat is only 5.5 J / g, the temperature difference is as high as 66°C, and the extractable content increases to 8.1%.

[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A heat storage polyamide composition, characterized in that: The composition comprises the following components calculated by weight: 23-75 parts of polyamide resin; 5 to 25 parts of coated phase change microcapsules; 20-50 parts of compatibilizer; Processing aids 0-10 parts; The coated phase change microcapsules are PP grafted maleic anhydride coated phase change microcapsules; the mass ratio of the phase change microcapsules to the PP grafted maleic anhydride is 1:(0.05-0.2); the shell of the phase change microcapsules is polyurethane.

2. The heat storage polyamide composition according to claim 1, characterized in that: The coating rate of the coated phase-change microcapsules is 3-6%.

3. The heat storage polyamide composition according to claim 1, characterized in that: The core material of the phase-change microcapsule is alkane paraffin and / or higher fatty alcohol; the carbon number of the alkane is 18 to 30; the higher fatty alcohol is a monohydric alcohol with a carbon number higher than 12 and a mixture thereof.

4. The heat storage polyamide composition according to claim 1, characterized in that: The maleic anhydride grafting rate of the PP grafted with maleic anhydride is 0.3-1.5%.

5. The heat storage polyamide composition according to claim 1, characterized in that: The compatibilizer is one or more of PP grafted maleic anhydride, POE grafted maleic anhydride or EPDM grafted maleic anhydride.

6. The heat storage polyamide composition according to claim 1 or 2, characterized in that: The preparation method of the coated phase change microcapsule is as follows: Heat and mix water and phase change microcapsules, add PP grafted maleic anhydride and stir evenly, raise the temperature to 75-85°C and stir to react, then cool down, filter and dry in sequence to obtain coated phase change microcapsules.

7. The heat storage polyamide composition according to claim 1, characterized in that: The processing aids include lubricants and / or antioxidants.

8. The method for preparing the heat storage polyamide composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polyamide resin, the coated phase change microcapsules, the compatibilizer and the processing aid are mixed, melt-blended and extruded to obtain a heat storage polyamide composition.

9. Use of the heat storage polyamide composition according to any one of claims 1 to 7 in the fields of building materials and energy storage materials.

Citation Information

Patent Citations

  • Preparation method of aromatic polyamide core-shell paraffin phase change microcapsule

    CN101982231A

  • High-temperature-resisting nylon composite material and preparation method thereof

    CN108727815A